Enteral Nutrition in Operated-On Gastric Cancer Patients: An Update. - Triantafillidis, John K; Papakontantinou, John; Antonakis, Pantelis; Konstadoulakis, Manousos M; Papalois, Apostolos E (Nutrients, 2024)
It is well established that the preoperative nutritional status of gastric cancer (GC) patients significantly affects the prognosis of the operated patients, their overall survival, as well as the disease-specific survival. Existing data support that preoperative assessment of nutritional status and early correction of nutritional deficiencies exert a favorable effect on early postoperative outcomes. A variety of relevant indices are used to assess the nutritional status of GC patients who are candidates for surgery. The guidelines of almost all international organizations recommend the use of oral enteral nutrition (EN). Oncologically acceptable types of gastrectomy and methods of patient rehabilitation should take into account the expected postoperative nutritional status. The majority of data support that perioperative EN reduces complications and hospital stay, but not mortality. Oral EN in the postoperative period, albeit in small amounts, helps to reduce the weight loss that is a consequence of gastrectomy. Iron deficiency with or without anemia and low serum levels of vitamin B12 are common metabolic sequelae after gastrectomy and should be restored. EN also significantly helps patients undergoing neoadjuvant or adjuvant antineoplastic therapy. The occurrence of the so-called "postgastrectomy syndromes" requires dietary modifications and drug support. This review attempts to highlight the benefits of EN in GC patients undergoing gastrectomy and to emphasize the type of necessary nutritional management, based on current literature data.
Keywords: Enteral Nutrition; Gastrectomy; Humans; Malnutrition; Nutrition Assessment; Nutritional Status; Postgastrectomy Syndromes; Postoperative Complications; Stomach Neoplasms